The Equivalence of Liquidity Preference and Loanable Funds Theories in Stock-Flow Economies: A Comment - Ruffin, R. J. (Review of Economic Studies, 1967)
Journal Article The Equivalence of Liquidity Preference and Loanable Funds Theories in Stock-Flow Economies: A Comment Get access R. J. Ruffin R. J. Ruffin Washington State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 4, October 1967, Pages 420–421, https://doi.org/10.2307/2296561 Published: 01 October 1967